Habitations of the Veil : Metaphor and the Poetics of Black Being in African American Literature - Fisher, Rebecka Rutledge, 1965- (Book collections on Project MUSE., 2014)
"A hermeneutical study of metaphor in African American literature"--Provided by publisher